1995
DOI: 10.1093/oxfordjournals.humrep.a136256
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of a case of ‘complete septate uterus with unilateral haematometra’

Abstract: Endoscopy and ultrasound was used to diagnose a 13 year old virgin girl who presented with dysmenorrhoea and suspected right side adnexal tumescence. The girl was found to have a complete septate uterus with non-communicating right hemicavity and haematometra, an exceptional type of Müllerian anomaly. After pretreatment with buserelin, hysteroscopic metroplasty was successfully performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For nonseparated horns, bleeding and compromise of the wall thickness of the uterine unicornis can occur, and extirpation may best be done by laparotomy. Hysteroscopic resection of the midline septum in nonseparated, noncommunicating horns, with drainage of hematometra and ablation of endometrial tissue, has been reported, [141][142][143] with or without homologous salpingectomy. The incidence of transperitoneal migration of gametes in humans is high, so it is important to decrease the risk of ectopic pregnancy by removing the homologous tube.…”
Section: Resultsmentioning
confidence: 99%
“…For nonseparated horns, bleeding and compromise of the wall thickness of the uterine unicornis can occur, and extirpation may best be done by laparotomy. Hysteroscopic resection of the midline septum in nonseparated, noncommunicating horns, with drainage of hematometra and ablation of endometrial tissue, has been reported, [141][142][143] with or without homologous salpingectomy. The incidence of transperitoneal migration of gametes in humans is high, so it is important to decrease the risk of ectopic pregnancy by removing the homologous tube.…”
Section: Resultsmentioning
confidence: 99%
“…Open as well as minimally invasive treatments have been described [2,3,9]. The goals of treatment are drainage of the hematometra, prevention of its recurrence and drainage/excision of adnexal endometriomas.…”
Section: Discussionmentioning
confidence: 99%
“…The goals of treatment are drainage of the hematometra, prevention of its recurrence and drainage/excision of adnexal endometriomas. Recurrence of hematometra can be prevented by a complete excision of the obstructed cavity with preservation of the normal cavity or by ablation of the functional endometrium in the obstructed uterine cavity or by a unification of both uterine cavities by incising the septum [2,6,9,10]. In cases with associated adnexal endometriomas and associated adhesions, open laparotomy may be a better approach as adequate clearance of adnexal endometriomas can be done using open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery can be done by open or minimally invasive method; definitive surgery involves drainage of hematometra and excision of blind non-communicating hemiuterus taking care to maintain integrity of functional communicating hemiuterus and cervix. 8,9 …”
Section: Discussionmentioning
confidence: 99%